Use of urease inhibitors to reduce ammonia volatilization in Amazonian soils - Barberena, Iara Magalhães; Espindula, Marcelo Curitiba; Araújo, Larissa Fatarelli Bento de; Marcolan, Alaerto Luiz (Pesquisa Agropecuaria Brasileira, 2019)
The objective of this work was to evaluate urease inhibitors for the reduction of ammonia volatilization in Amazonian soils. The work was carried out on a clayey yellow Oxisol, a clayey red Oxisol, and on a light silty Ultisol. Each experiment was conducted in split plots, using standard urea, urea + a benzimidazole-type urease inhibitor (BZI1), urea + a benzoylthiourea-type urease inhibitor (RTB68), urea + N-(n-butyl) triamide thiophosphate (NBPT), or a fertilizer-free control. Volatilized ammonia was collected at 48, 96, 144, 192, 240, 288, 336, and 384 hours after fertilization. Ammonia volatilization reached a maximum at 144 hours in the urea, urea + benzimidazole, and urea + benzoylthiourea treatments. A peak level was reached at 192 and 288 hours in the urea + N-(n-butyl) triamide thiophosphate treatment. In yellow Oxisols, benzimidazole and benzoylthiourea reduced the ammonia losses by 22 and 10%, respectively, in soils without urease inhibitors. However, neither of these agents significantly reduced ammonia volatilization at the rate determined for standard urea in red Oxisols or Ultisols. N-(n-butyl) triamide thiophosphate is the most efficient urease inhibitor for the soils of southwestern Amazonia.